PENGEMBANGAN BUKU GEOMETRI TERINTEGRASI JAJANAN TRADISIONAL BERBASIS AR UNTUK MENINGKATKAN KEMAMPUAN SPASIAL - Febriyanto, Eko Yudi Febriyanto; Yudianto, Erfan; Ambarwati, Reza; Kurniati, Dian; Safrida, Lela Nur; Firmansyah, Frenza Fairuz; Fazira, Shima Kunaza (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2025)
Student must have spatial ability in order to understand geometry material well. Students with low spatial ability will find it difficult to understand geometry. The application of AR such as Assemblr Edu with the integration of traditional snacks is a solution to improve students’ spatial ability. This study aims to describe the process and results of developing an AR-based geometry book integrated with traditional snacks to improve students’ spatial ability. The research method is R&D with the ADDIE model. Data were collected using questionnaire and test method, with validation sheet instruments, readability test questionnaires, student response questionnaires, and spatial ability tests that had been validated before use. Geometry books are arranged according to spatial ability indicators: spatial perception, spatial visualization, and mental rotation. The trial was conducted on grade IX junior hidh school students. The results showed that geometry books were valid (2.84), practical (81.7%), and effective in improving students’ spatial ability with 93.8% of students reaching the minimum moderate category. So, AR-based geometry books integrated with traditional snacks can improve students’ spatial ability. Further research is recommended to explore AR application with 3D object decomposition features and cross-cultural integration to test the adaptation of books in different regional contexts.